Sky in the deep - Young, Adrienne, 1985- (Wednesday Books, 2018)
Raised to be a warrior, seventeen-year-old Eelyn fights alongside her Aska clansmen in an ancient rivalry against the Riki clan, but when faced with her brother's betrayal, and driven by a growing love for her brother's friend Fiske, she attempts to unite the two clans.